2013
DOI: 10.2807/ese.18.17.20464-en
|View full text |Cite
|
Sign up to set email alerts
|

Severe Seoul hantavirus infection in a pregnant woman, France, October 2012

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
0
8
1
Order By: Relevance
“…We recovered seven complete and semi-complete genomes of SEOV from these wild rats, which greatly increase the genetic data available on SEOV from France, especially for the M and L segments. The recovered genomes were significantly larger in contrast to the previous studies (11)(12)(13). Genetic analyses showed high identity levels between all these (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We recovered seven complete and semi-complete genomes of SEOV from these wild rats, which greatly increase the genetic data available on SEOV from France, especially for the M and L segments. The recovered genomes were significantly larger in contrast to the previous studies (11)(12)(13). Genetic analyses showed high identity levels between all these (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 74%
“…The presence of SEOV in France has been detected in both humans and rats previously (11,12). The first SEOV-HFRS case detected in Europe, confirmed by molecular evidence, was found in a pregnant woman from Replonges (12), a locality close to Lyon, a densely populated city with over 500,000 inhabitants in France. Since then, several studies have demonstrated SEOV circulation in Lyon city area.…”
Section: Introductionmentioning
confidence: 90%
“…More importantly, close monitoring of fetal life signs and the appreciation of obstetric disposition are pivotal to both the mother and fetus during pregnancy. By reviewing the previous literature, we found that four pregnant women with HFRS were complicated with severe fetal adverse events but still recovered fully after terminating the pregnancy ( 13 , 15 , 16 , 33 ). Of the three pregnant women experiencing intrauterine fetal death in current study, the two patients who selected timely termination recovered completely; However, the remaining patient refused to terminate pregnancy and subsequently died of DIC.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of adverse fetal events was more likely related to the severe status of pregnant women with HFRS. Previous literature showed that the cases with fetal adverse events were all classified into severe or critical type ( 13 , 15 , 16 ). In current cohort, three cases resulted in intrauterine fetal death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation